Rituximab‐induced acute lympholysis and pancytopenia after COVID‐19 vaccination. Issue 8 (16th August 2021) - Leung, Victoria S.; Lin, Yuankai
Abstract: Rituximab and COVID‐19 vaccine can cause massive hyperacute depletion of B cells and plasma cells, as well as subsequent cytokine release syndrome, coagulopathy, and pancytopenia. These effects differ from the adverse effects that have been reported for rituximab, and new guidelines regarding the timing of rituximab infusion and vaccination are urgently needed. Abstract : Rituximab and COVID‐19 vaccine can cause massive hyperacute depletion of B cells and plasma cells, as well as subsequent cytokine release syndrome, coagulopathy, and pancytopenia. These effects differ from the adverse effects that have been reported for rituximab, and new guidelines regarding the timing of rituximab infusion and vaccination are urgently needed.